Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.21873/anticanres.11827
|View full text |Cite
|
Sign up to set email alerts
|

HIF1α-associated circDENND4C Promotes Proliferation of Breast Cancer Cells in Hypoxic Environment

Abstract: CircDENND4C is a HIF1α-associated circRNA promoting the proliferation of breast cancer cells under hypoxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 11 publications
0
49
1
Order By: Relevance
“…However, reports of this model in breast cancer are very limited. Tang et al revealed that circRNA-001982 promotes breast cancer cell carcinogenesis by decreasing miR-143 expression ( 39 ); Liang et al suggested that circRNA-DENND4C promoted the proliferation of breast cancer cells in a hypoxic environment ( 40 ). In this study, miR-449a showed a complementary sequence to circRNA-000911 based on bioinformatics analysis, and this miRNA was finally identified as the endogenous competing RNA by luciferase reporter assay and RIP assay.…”
Section: Discussionmentioning
confidence: 99%
“…However, reports of this model in breast cancer are very limited. Tang et al revealed that circRNA-001982 promotes breast cancer cell carcinogenesis by decreasing miR-143 expression ( 39 ); Liang et al suggested that circRNA-DENND4C promoted the proliferation of breast cancer cells in a hypoxic environment ( 40 ). In this study, miR-449a showed a complementary sequence to circRNA-000911 based on bioinformatics analysis, and this miRNA was finally identified as the endogenous competing RNA by luciferase reporter assay and RIP assay.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, circRNAs regulated by hypoxia in endothelial cells were identified for the first time [102]. Subsequently, in breast cancer cells, HIF1α was reported to be crucial for upregulating circDENND4C under hypoxic conditions, indicating that circDENND4C is an HIF1α-associated circRNA and promotes the proliferation of breast cancer cells [115] . Under hypoxia, loss-of-function experiments indicate that circDENND4C knockdown could suppress glycolysis, migration and invasion by increasing miR-200b and miR-200c in breast cancer cells [116].…”
Section: Hypoxia Regulates Circrna Productionmentioning
confidence: 99%
“…There are currently few reports describing the role of circRNAs in breast cancer. Liang G et al reported that circDENND4C is a HIF1α-associated circRNA promoting the proliferation of breast cancer under hypoxia [ 3 ]. Lu L et al provided a profile of circRNAs in breast cancer and adjacent normal-appearing tissues [ 4 ].…”
Section: Introductionmentioning
confidence: 99%